The Implementation of the Reading to Learn Strategies in the Teaching of Short Stories Reading Compehension Achievement at SMPN 3 Medan - Masitowarni Siregar; Baharuddin; Endang Matulissa; Nelly Marlina Tampubolon Lili Sartika; Dimas Hendrawan (LingLit Journal Scientific Journal for Linguistics and Literature, 2021)
The aim of this endeavour is to find out: (1) Planning for learning about short stories using the Reading to Learn Approach); (2) Implementation of learning Short Stories using the Reading to Learn Approach. This study uses a qualitative descriptive method that emphasizes the process and meaning of ongoing activities. Data were collected through observation, field notes, interviews, and document analysis. Data validity was carried out through method triangulation and source triangulation. The research findings indicated that the teacher had carried out good preparation in planning R2L-based learning, namely by preparing learning preparataions in lesson plans formats, teaching materials, worksheet, assessments and learning media, The teacher also informs the students beforehand that the teacher would implement a new learning model in which it is hoped that all students would fully participate in the class later. At the implementation stage of learning the teacher had followed the R2L learning steps by Rose and Martin (2012), namely Preparation, Detailed Reading, Joins Construction and Individual Construction.